Influence of annealing temperature on structural and magnetic properties of MnFe2O4 nanoparticles - Surowiec Zbigniew (Nukleonika, 2015)
Nanoparticles of manganese ferrite were obtained by the impregnation of highly ordered mesoporous MCM-41 silica support. The investigated sample contained 20% wt. Fe. The obtained nanocrystallites were strongly dispersed in silica matrix and their size was about 2 nm. The sample annealing at 500°C led to increase of particle size to about 5 nm. The Mössbauer spectroscopy investigations performed at room temperature show on occurrence of MnFe2O4 nanoparticle in superparamagnetic state for the sample annealed in all temperatures. The coexistence of superparamagnetic and ferromagnetic phase was observed at liquid nitrogen temperature. The sample annealed at 400°C and 500°C has bigger manganese ferrite particle and better crystallized structure. One can assign them the discrete hyperfine magnetic field components.